ADAPTATION OF PUBLIC SERVICES IN THE ERA OF COVID 19 - Victor, Muhammad Wilson; Adnan, Ricardi S (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The success of public service organizations in the Covid 19 Era is greatly influenced by the ability to adapt to social changes that occur. This study illustrates how adaptation in public services in the Covid 19 era has shifted to serving via digital or online. The changes that have occurred have resulted in changes in people's behavior due to the implementation of the covid 19 protocol and government policies in handling Covid-19 during the pandemic. With the existing limitations, public services must be ensured to continue to run effectively and optimally so that the quality of public services provided remains. This study uses a literature review approach which is part of the qualitative type. In collecting research data, researchers utilize some literature, both library research and field research, which are primary and secondary. By combining all findings, both theories, models, and concepts of public service transformation to the changes that occur. This is done to provide input on existing Public ServicesKeywords: Public Service, Covid 19